Enhancing Sustainable Herd Structure Management in Thai Dairy Cooperatives Through Dynamic Programming Optimization - Thana Sarttra; Tossapol Kiatcharoenpol (My University, 2025)
Herd management plays a vital role in boosting the productivity, profitability, and sustainability of dairy cooperatives, particularly in developing countries where smallholder farmers are prevalent and have limited access to modern farming technologies. This research presents a dynamic programming (DP) model aimed at helping dairy cooperatives optimize decisions regarding herd structure, specifically focusing on strategies for culling and replacement to match milk supply with varying market demands. The model considers essential traits of dairy cows, including age, milk production, and reproductive condition, to ascertain the best transitions within the herd over several periods. Findings indicate that implementing the proposed DP model can effectively align milk output with fluctuating demand, decrease the gap between supply and demand, and enhance overall herd productivity. While this study uses Thai dairy cooperatives as a case study, the developed model and its insights are relevant to similar smallholder dairy systems in other developing countries, thereby aiding improved decision-making and promoting sustainable herd management practices worldwide.
Keywords: Cooperative Studies and Economics